Forms of financial fraud in the modern world - I. I. Rakhmeeva; S. V. Popkova (Цифровая социология, 2025)
As a result of highly developed modern information systems and technologies, cases of fraud have become more frequent and new schemes of fraud appear. The purpose of this study is to describe the phenomenon of financial fraud in the modern digital world and behaviour of citizens who are subjected to fraudulent deception attempts for the subsequent development of recommendations to combat it. The main research method is a sociological survey. The base is made of students from the economic university as a social group with a higher level of financial and digital literacy. The survey concluded that phone calls are the most common form of fraud. Financially literate people are critical of calls from unfamiliar numbers and information that the opponent reports. On the other hand, the confidence that a competent person will not become a victim of fraud reduces the need for knowledge about actions after the theft of funds. Recommendations are made that citizens should be more attentive and critical of suspicious information and calls to perform any actions in the Internet space or by phone; the state should inform citizens about forms of fraud, ensure greater detection of crimes and protection of assets of the Russians and organisations; in turn, firms should intensively protect their information portals, inform customers about possible actions of fraudsters and methods for protecting their personal data.